Penyelesaian Sengketa Pertanahan Gedung Olahraga (GOR) Tanjungbalai di Pengadilan Negeri Tanjungbalai - Aqmarina, Ifni; Pratiwi, Irda (Sekolah Tinggi Ilmu Hukum Prof Gayus Lumbuun, 2024)
Land holds great importance for all individuals, including personal individuals (natuurlijk persoon) with ownership rights and public entities (rechtpersoon). Both are recognized as legal subjects with land as the object of their legal rights. The significance of land lies in its use for agriculture, settlements, commercial buildings like shops and structures, and other developments. This research focuses on the land dispute resolution process at the Tanjungbalai Sports Hall (GOR) in the Tanjungbalai District Court. The aim is to explore the factors considered by the panel of judges in making decisions on land disputes in the court. An empirical legal research method is used with a case study at the Tanjungbalai District Court Office. This study primarily relies on legal materials such as regulations, supplemented by secondary sources like legal books, and tertiary sources like non-legal books. Non-litigation dispute resolution is necessary to achieve a beneficial resolution for both parties. This applies to all cases brought to the District Court. Mediation or non-litigation dispute resolution aims for the parties to reach mutually beneficial agreements with the assistance of a neutral third party. However, ultimately, the parties themselves make the final decision. The settlement process is carried out through two mechanisms, namely compensation payments. In this case, the applicant demands compensation of 17 million, while the defendant requests 6 million. Despite reports that a budget of 9.6 billion is available, the Tanjungbalai City Government suddenly withdrew and refused to pay the agreed compensation. In deciding this case, the Judge must consider and prioritize the principles of justice, legal certainty, and practicality to reach an ideal, win-win decision that does not burden either party and is well accepted.